2023
DOI: 10.3390/foods12142652
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screening of Microalgae as Potential Sources of Natural Antioxidants

Abstract: In order to rapidly screen microalgae species as feedstocks for antioxidants, extracts were obtained from 16 microalgae strains (under 11 genera, 7 classes) using two methods: a one-step extraction with ethanol/water and a three-step fractionating procedure using hexane, ethylacetate, and water successively. Measuring the total phenol content (TPC), total carotenoid content (TCC), and antioxidant activity of the extracts, indicating TPC and TCC, played an important role in determining the antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Wang et al . (2023) reported that FRAP of A. platensis varied when it was extracted using different solvents, but ethanol/water fraction showed a higher FRAP activity than hexane and ethyl acetate fractions. Another study showed similar results that FRAP of S. platensis extracted using polar solvent assisted with microwave was higher than those extracted using non‐polar solvent (Esquivel‐Hernández et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al . (2023) reported that FRAP of A. platensis varied when it was extracted using different solvents, but ethanol/water fraction showed a higher FRAP activity than hexane and ethyl acetate fractions. Another study showed similar results that FRAP of S. platensis extracted using polar solvent assisted with microwave was higher than those extracted using non‐polar solvent (Esquivel‐Hernández et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae exhibit abundance in pigments, phenols, polysaccharides, proteins, essential fatty acids, vitamins, and other bioactive nutrients of high value, thereby presenting a potent repository of natural antioxidants. Notably, while the prevailing market for natural antioxidants predominantly relies on land plants, antioxidants derived from microalgae are presently not widely available [ 11 ]. Nevertheless, microalgae hold promise as a prospective source of natural antioxidant products due to their greater yield compared to terrestrial plants and the controllability of their culture conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been considerable scienti c interest in identifying safe and natural exogenous antioxidant alternatives (Wang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For some time, terrestrial plants have been recognised as sources rich in antioxidants such as carotenoids, phenols and vitamins (Ferdous and Yusof 2021; Wang et al 2023). More recently, microalgae have emerged as potent and sustainable alternative sources with the capacity to produce diverse bioactive metabolites (Zhong and Shahidi 2015; Wang et al 2023). Several microalgal species such as Chlorella sp., Arthrospira sp.…”
Section: Introductionmentioning
confidence: 99%